Making sense while steering through the fog: Principals’ metaphors within a national reform implementation - Ganon-Shilon, Sherry; Schechter, Chen (Education Policy Analysis Archives, 2017)
Principals’ implementation of national reforms in the educational arena resembles a wild ride on a roller coaster as they face with contradicting demands, ongoing confusion and ambiguity. As critical change agents, principals interpret and translate reform demands into local practices through a process of sense-making. This current qualitative research explored 60 high school principals' sense-making processing of their leadership within a national reform through their use of metaphors. Data analysis yielded four themes: (a) reframing the principal’s role and pedagogical autonomy; (b) reframing the principal’s work; (c) reframing the school culture; and (d) reframing the principal’s relationships with teachers. This study expands the currently limited knowledge about principals' experience with and responses to reforms, and suggests implications and further research on metaphors principals use within reform implementation.